THE ROLE OF DIGITALIZATION IN EDUCATION - Nematulla Abdukarimovich Gulbayev; Aygul Tolgatovna Kuralbayeva; Arifjon Maxsudovich Khodjayev (European Science Publishing, 2024)
The article analyzes the role of digitization in education based on the experience of the authors, paying attention to the problems of applying digital technologies to the educational process.
Keywords: information, digitization of education, education, lesson, technology.